764 Expansion with IL-15 increases cytotoxicity of Vγ9Vδ2 T cells and is associated with higher levels of cytotoxic molecules and T-bet. (9th November 2020) - Aehnlich, Pia; Straten, Per Thor; Carnaz Simoes, Ana Micaela; Skadborg, Signe; Olofsson, Gitte
Abstract : Background: Adoptive cell therapy (ACT) is an approved treatment option for certain hematological cancers and has also shown success for some solid cancers. Still, benefit and eligibility do not extend to all patients. ACT with Vγ9Vδ2 T cells is a promising approach to overcome this hurdle. Methods: In this study, we explored the effect of different cytokine conditions on the expansion of Vγ9Vδ2 T cells in vitro. Results: We could show that Vγ9Vδ2 T cell expansion is feasible with two different cytokine conditions: (a) 1000U/ml interleukin (IL)-2 and (b) 100U/ml IL-2+100U/ml IL-15. We did not observe differences in expansion rate or Vγ9Vδ2 T cell purity between the conditions; however, IL-2/IL-15-expanded Vγ9Vδ2 T cells displayed enhanced cytotoxicity against tumor cells, also in hypoxia. While this increase in killing capacity was not reflected in phenotype, we demonstrated that IL-2/IL-15-expanded Vγ9Vδ2 T cells harbor increased amounts of perforin, granzyme B and granulysin in a resting state and release more upon activation. IL-2/IL-15-expanded Vγ9Vδ2 T cells also showed higher levels of transcription factor T-bet, which could indicate that T-bet and cytotoxic molecule levels confer the increased cytotoxicity. Conclusions: These results advocate the inclusion of IL-15 into ex vivo Vγ9Vδ2 T cell expansion protocols in future clinical studies.